Development of Tajweed Learning Videos in Qur'an Hadith Subject to Improve Students' Understanding of Mad Reading Rules at Madrasah Tsanawiyah - Darain, A. Sa’dud; Sa’diyah, Halimatus; Aini, Intan Nur; Juhairiyah; Anshari, Achmad (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
This study aims to develop a tajweed learning video in the Qur’an Hadith subject, specifically on mad reading rules (Mad Thabi’i, Mad Wajib Muttashil, and Mad Jaiz Munfashil), and to evaluate its feasibility and effectiveness in enhancing students’ understanding. The research employed a Research and Development (R&D) method, including expert validation and limited trials involving seventh-grade students at Madrasah Tsanawiyah. The results indicate that the developed video is both feasible and effective for tajweed learning. Its integrated visual and auditory approach helps students grasp tajweed concepts both theoretically and practically. Expert validation scored above 85%, while student responses were highly positive in terms of comprehension, engagement, and content clarity. Penelitian ini bertujuan untuk mengembangkan video pembelajaran tajwid pada mata pelajaran Al-Qur’an Hadis, khususnya materi hukum bacaan mad (Mad Thabi’i, Mad Wajib Muttashil, dan Mad Jaiz Munfashil), serta mengevaluasi kelayakan dan efektivitasnya dalam meningkatkan pemahaman siswa. Metode yang digunakan adalah Research and Development (R&D), mencakup tahap validasi ahli dan uji coba terbatas pada siswa kelas VII Madrasah Tsanawiyah. Hasil penelitian menunjukkan bahwa video yang dikembangkan layak digunakan dan efektif mendukung pembelajaran tajwid. Pendekatan visual dan auditori yang terintegrasi membantu siswa memahami teori dan praktik tajwid secara lebih konkret. Validasi ahli menunjukkan skor kelayakan di atas 85%, dan respons siswa sangat positif dalam hal pemahaman, ketertarikan, dan kejernihan materi.